THE USE OF KAHOOT APPLICATION AT THE OPENING OF A WORKSHOP - Derthasari Rupidara, Grace; Artheza, Christa; Dwi Nastiti, Fadhylah; Annisa Intan Putri, Rizky; CM Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays the use of a technology is no longer unfamiliar. Technologyy sophistication offers many applications that can be used by lecturers and students to improve their abilities. One application that can be used to motivate the students in an opening and closing a workshop is the Kahoot application. Game Education Program by utilizing the Kahoot Application Program in Teaching and Learning Process, is a learning method that involves all students and teachers or lecturers in the learning process towards a meaningful learning that can be accessed online. This application is very effective in opening of a workshop and to keep the participants or the students stay focused and also can increase their interest to the workshop. The purposes of this study are, first to identify how to implement the use of the Kahoot application, second is to know the benefits of the Kahoot application in the process of opening a workshop, in creating an innovative and creative learning, to achieve the effectiveness of learning, and to make a fun learning. The methodology in this study uses the Descriptive Research Method by experimenting the using of Kahoot at a Workshop at the Islamic University, Widyatama University and also at STIA Bandung. The results of this study that the use of the Kahoot application can motivate the students to stay focused on the workshop, adding their insights, knowledges, and to make the workshop become an effective one.